TECHNOLOGICAL ASPECTS IN THE CONSTRUCTION OF PROSTHETIC REHABILITATION WITHOUT METAL FRAMEWORK - Diana Diaconu; Monica Tatarciuc; Andrei Melinte; Anca Viţalariu (Romanian Dental Association for Education, 2013)
Ceramic materials tend to replace, in recent years, other restorative materials used for prosthetic constructions, due to their special properties (biocompatibility, mechanical resistance greater longevity over time, chemical and dimensional stability). The newest materials on zirconium basis, enriched with yttrium and alumina-based ceramic continues to be studied. Clinical studies have shown that the most common cause of failures in all ceramic prosthesis is the fracture of plating material. The question that was put in that situation was whay could be the cause- the different behavior of the two materials or insufficient knowledge of the quality of the interface of zirconia-ceramic. In the present article we wanted to illustrate two methods for the prosthetic ceramic restorations on the zirconium framework. Choosing the best material for the realisation of prosthetic constructions, so as to be satisfied both requirements of aesthetic and biomechanical, is a decision of the dental team - in accordance with the wishes of the patient and the clinical situation